An Economic Evaluation of Community and Residential Aged Care Falls Prevention Strategies in NSW - Church, J.; Goodall, S.; Norman, Richard; Haas, M. (NSW Health, 2011)
Aim: To evaluate the cost-effectiveness of strategies designed to prevent falls amongst people aged 65 years and over living in the community and in residential aged-care facilities.Methods: A systematic review and meta-analysis of the literature was conducted. The pooled fall rate ratio was used in a decision analytic model that combined a Markov model and decision tree to estimate the costs and outcomes of potential interventions and/or strategies. The resulting cost per quality-adjusted life year was estimated.Results: The most cost-effective falls prevention strategy in community-dwelling older people was Tai Chi. Expedited cataract surgery and psychotropic medication withdrawal were also found to be cost-effective; however, the effectiveness of these interventions is less certain due to small numbers of trials and participants. The most costeffective falls prevention strategies in residential aged-care facilities were medication review and vitamin D supplementation.